Characterization of expression, activity and role in antibacterial immunity of Anopheles gambiae lysozyme c-1 - Kajla, Mayur K. (2010)
There are eight lysozyme genes in the Anopheles gambiae genome. Transcripts of one of these genes, LYSC-1, increased in Anopheles gambiae cell line 4a3B by 24 h after exposure to heat-killed Micrococcus luteus. Lysozyme activity was also identified in conditioned media from the cell line from which the protein was purified to homogeneity using ion exchange and gel filtration. Mass spectrometric analysis of the purified protein showed 100% identity to lysozyme c-1. Purified lysozyme c-1 was tested against non-mosquito derived as well as culturable bacteria isolated from mosquito midguts. Lysozyme c-1 had negligible effects on the growth of most mosquito-derived bacteria in vitro but did inhibit the growth of M. luteus. Although Lys c-1 did not directly kill most bacteria, knockdown of LYSC-1 resulted in significant mortality in mosquitoes subjected to hemocoelic infections with Escherichia coli but not M. luteus thus suggesting that this protein plays an important role in antibacterial defense against selected bacteria.